2022
DOI: 10.1021/acs.biomac.1c01630
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Profiling of the Functional Heterogeneity of Technical Lignins

Abstract: In technical lignins, functionality is strongly related to molar mass. Hence, any technical lignin exhibits concurrent functionality-type distribution (FTD) along its molar mass distribution (MMD). This study combined preparative size-exclusion chromatography with offline characterizations to acquire highly resolved profiles of the functional heterogeneity of technical lignins, which represent crucial information for their material use. The shape of these profiles showed considerable dissimilarity between diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 54 publications
0
21
0
Order By: Relevance
“…This obstacle is further complexed by lignin species obtained from different raw materials with various phenylpropanoid monomer unit ratios, resulting essentially in a cluster of copolymers . Additionally, interactions of lignin molecules with the stationary phase are almost inevitable due to its three-dimensional and intrinsic branched structure, which can prolong the elution time and consequently lead to misleading molar masses. , In this context, the aggregation of lignin molecules by intermolecular forces, especially initiated by hydrogen bonding of hydroxyl groups, has been discussed earlier . Furthermore, it has been reported that clustering of lignin aggregates occurs due to the π–π interaction between the aromatics .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…This obstacle is further complexed by lignin species obtained from different raw materials with various phenylpropanoid monomer unit ratios, resulting essentially in a cluster of copolymers . Additionally, interactions of lignin molecules with the stationary phase are almost inevitable due to its three-dimensional and intrinsic branched structure, which can prolong the elution time and consequently lead to misleading molar masses. , In this context, the aggregation of lignin molecules by intermolecular forces, especially initiated by hydrogen bonding of hydroxyl groups, has been discussed earlier . Furthermore, it has been reported that clustering of lignin aggregates occurs due to the π–π interaction between the aromatics .…”
Section: Introductionmentioning
confidence: 99%
“…Classifying the size and chemistry by (solvent) fractionation leads to classes of more homogeneous lignin molecules, which will most likely influence the d n /d c value. Additionally, technical lignins can exhibit absorption (and fluorescence) behavior. , Once the sample absorbs incident light, this can cause a change in the scattered intensity and lead to misleading calculation in the MW. In a recent work, Zinovyev et al discussed the dependency of the d n /d c value on the MW and the absorption phenomena for Kraft lignin and fractions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Its aromatic structure is composed of three basic phenylpropane units, guaiacyl (G-unit), syringyl (S-unit), and p -hydroxyphenyl (H-unit), which are derived from coniferyl, sinapyl, and p -coumaryl alcohol, respectively . These units are linked by carbon–carbon (β–5, 5–5, β–1, and β–β) and carbon–oxygen linkages (β–O–4, α–O–4, and 4–O–5), forming an amorphous and complex three-dimensional structure with a variety of functional groups, such as carbonyl, methoxyl, and aliphatic and phenolic hydroxyl groups. , Among the functional groups, the hydroxyls are the most abundant and most reactive and therefore the preferred target for reactions to develop lignin-based materials, such as PUs. Furthermore, the abundant aromatic moieties impart high stiffness to lignin .…”
Section: Introductionmentioning
confidence: 99%